2019
DOI: 10.1016/j.engfailanal.2018.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear finite element analysis for structural capacity of railway prestressed concrete sleepers with rail seat abrasion

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 17 publications
(18 reference statements)
0
22
0
Order By: Relevance
“…In this study, customised combinations of different hidden neurons (1,5,10,15,20,25,30), hidden layers (1-2) and LM, BR and SCG algorithms have been employed. Furthermore, each pattern of ANN architectures has been trained for five times to improve the accuracy of models.…”
Section: Performance Evaluation Of Ann Architecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, customised combinations of different hidden neurons (1,5,10,15,20,25,30), hidden layers (1-2) and LM, BR and SCG algorithms have been employed. Furthermore, each pattern of ANN architectures has been trained for five times to improve the accuracy of models.…”
Section: Performance Evaluation Of Ann Architecturesmentioning
confidence: 99%
“…Research articles have shown a growth in the noise reduction coefficient with an increase in rubber replacing sand. Therefore, replacing aggregates with waste rubber in concrete at an opportune ratio not only supports the improvement of the performance of the concrete but also avoids the environmental pollution and waste of resources caused by conventional treatments [9,10]. The use of waste rubber can help engineers and stakeholders achieve a system's zero emission status in a faster and safer manner.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to other prestressed concrete (PC) members, the prestress of concrete sleepers will be lost after being transformed [34][35][36][37][38]. The prestress loss consists of both instantaneous losses and time dependent losses.…”
Section: The Calculation Of Prestress Lossesmentioning
confidence: 99%
“…In order to simulate a real ballast condition, a polymeric material can be placed between the rail seats of sleepers as an alternative test support specified in Australian Standard AS1085.19J [33][34][35][36][37][38]. It is found that 5 layers of rubber conveyor matting used in the mining industry is enough to avoid excessive vibrations from the floor.…”
Section: Experimental Modal Analysismentioning
confidence: 99%